Serotype distribution of invasive and non-invasive pneumococcal disease in adults ≥65 years of age following the introduction of 10- and 13-valent pneumococcal conjugate vaccines in infant national immunization programs: a systematic literature review - Izurieta, Patricia; Borys, Dorota (Frontiers in Public Health, 2025)
IntroductionDespite the widespread implementation of 10- and 13-valent pneumococcal conjugate vaccines (PCVs) in infant national immunization programs and anticipated herd effects, pneumococcal disease incidence remains relatively high among older adults. In this vulnerable population, this includes not only invasive pneumococcal disease (IPD), but, more notably, non-invasive community-acquired pneumonia (CAP). A comprehensive understanding of adult pneumococcal epidemiology, particularly that of non-invasive CAP, is essential to guide future vaccination strategies for this population.MethodsWe systematically reviewed observational studies (2006–2020) on pneumococcal serotype distribution in IPD and non-invasive CAP among adults aged ≥65 years after PCV implementation in children, focusing on the period post-implementation of the 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) and 13-valent PCV (PCV13). Serotype-specific pooled percentage averages were calculated to determine the contribution of each serotype to a certain clinical manifestation.ResultsOur analysis of 17 IPD and 17 CAP studies indicates the persistence of several vaccine serotypes, particularly serotypes 3 and 19A, in both clinical manifestations. Also serotype 7F remained frequently reported. The predominant non-PCV13 serotypes identified in both manifestations were serotypes 8, 12F, 15A, and 22F.ConclusionThe persistence of certain PCV13-serotypes in pneumococcal disease among adults aged ≥65 years suggests that herd immunity by infant PCV immunization may be insufficient to provide optimal protection in this population. This, coupled with emerging non-PCV13 serotypes due to serotype replacement and other limitations of current vaccines, supports the need for new vaccination technologies and strategies to improve protection of older adults.